Maternal and foetal cardiovascular responses to a moderate-to-high intensity resistance exercise session - McCarthy, T. A.; Buckman, J. F.; Simonds, A. H.; Velez, S.; Spaeth, A. M. (Journal of Sports Sciences, 2025)
Foetal heart rate (FHR) >160 BPM is an indicator of foetal stress. FHR increases following high intensity aerobic training; however, resistance training is understudied. Investigate maternal and foetal responses to moderate-to-high intensity resistance exercise and determine whether recent exercise history affects responses. Thirty-seven individuals (31.8 ± 4.2y, pre-pregnancy BMI 23.7 ± 3.9, 28-32 weeks gestation) completed familiarization (Visit 1) and an 8-repetition maximum test (Visit 2) for squat, incline bench, deadlift, latissimus pull down, leg press and row and then underwent a training session of the same exercises at progressive intensities with maternal and foetal monitoring (Visit 3). Participants were categorized as physically active (PA, >150 min self-reported moderate-to-vigorous exercise/week (MVPA)) or not-physically active (NPA, <90 min MVPA). Peak FHR averaged 156.28.3 BPM, 90% CI [153.9-158.5 BPM] and exceeded 160 BPM for >2 mins in 15 (2.3%) instances. PA participants (n = 19) exhibited lower pre-exercise maternal heart rate (MHR, p = 0.04, d = 0.72), greater MHR change during the squat (p = 0.042, d = -0.69) and greater FHR change during the incline press (p = 0.046, d = -0.73), compared to NPA participants (n = 18). An acute bout of moderate-to-high intensity resistance exercise was well tolerated in pregnant individuals. Extra rest between sets is recommended to allow time for FHR to normalize.